Production of self-healing asphalt with steel short fibres and microwave heating: pilot study - Garcez, Monica Regina; Takimi, Antonio Shigueaki; Brykalski, Marilia (Acta Scientiarum. Technology, 2018)
This pilot study aims to develop a self-healing asphalt through microwave heating, to reduce processing time, save energy and allow real commercial applications in a near future. Asphalt based composites were produced with different percentages of steel short fibers, obtained from the cutlery industry, to serve as a heat source for microwave radiation. Structural characteristics, morphology, and thermic behavior of the short steel fibers were characterized through X-ray Diffraction, X-ray Fluorescence, Scanning Electron Microscopy and Thermogravimetric Analysis, that was also used to verify the relation between mass variation and temperature of the asphalt-based composite. Temperature was monitored during micro wave heating to determine the heating rate of the composites with different percentage of fibers. Brookfield viscosity, penetration, ductility, softening point and density tests were carried out to characterize physical properties of the most representative asphalt-based composite. Results show the feasibility to use microwave heating in the production of the composite, indicating potential for future application as self-healing asphalt and pavement repair. Â